2022
DOI: 10.1101/2022.07.13.499944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular and Anatomical Characterization of Parabrachial Neurons and Their Axonal Projections

Abstract: The parabrachial nucleus (PBN) is a major hub that receives sensory information from both internal and external environments. Specific populations of PBN neurons are involved in behaviors including food and water intake, pain sensation, breathing regulation, as well as learning and responding appropriately to threatening stimuli. However, it is unclear how many PBN neuron populations exist and how different behaviors may be encoded by unique signaling molecules or receptors. Here we provide a repository of dat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…The identity of PBN neurons engaged by CeA Htr2a neurons remains to be elucidated. The recent report on single cell transcriptomic mapping of PBN neurons will likely aid in this important endeavor (Pauli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The identity of PBN neurons engaged by CeA Htr2a neurons remains to be elucidated. The recent report on single cell transcriptomic mapping of PBN neurons will likely aid in this important endeavor (Pauli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that peptidergic neurons expressing CGRP (encoded by the Calca gene) in the external lateral parabrachial nucleus (PBel) and their direct downstream CGRP receptor-expressing neurons in the lateral subdivision of the central amygdala (CeAl) plays important roles in pain perception and threat learning in mice (Han et al, 2005; Han et al, 2015; Salmon et al, 2001; Sato et al, 2015). In addition to glutamate, CGRP neurons in the PBel (CGRP PBel ) co-express various neuropeptides, such as substance P (SP), pituitary adenylyl cyclase-activating peptide (PACAP), and neurotensin (NTS) (Kang et al, 2020; Palmiter, 2018; Pauli et al, 2022). However, the main transmitter that relays the US information in this peptidergic circuit was not known.…”
Section: Resultsmentioning
confidence: 99%
“…Since aversive sensory stimuli failed to trigger the SypSEP fluorescence increase at CGRP PBel→CeAl terminals, we investigated whether the glutamate release by CGRP PBel is dispensable in Pavlovian treat learning. To disturb glutamate release, we edited the Slc17a6 gene, which encodes Vglut2, using the CRISPR/saCas9 system (Hunker et al, 2020), based on a report showing that the Vglut2 is the main glutamate transporter in the PBel (Pauli et al, 2022). AAVs that express Cas9 and sgRNAs for Slc17a6 or Rosa26 (as control) in a Cre-dependent fashion were bilaterally injected into the PBel of Calca Cre/+ mice.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 9, 2023. ; https://doi.org/10.1101/2023.02.08.527340 doi: bioRxiv preprint PbN neurons respond to variety of noxious stimuli (8,(12)(13)(14) and function as a hub for the relay of nociceptive information to multiple brain regions, including the periaqueductal gray, hypothalamic and thalamic nuclei, the extended amygdala, and the central amygdala (CeA) (12,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%